The enduring agency of Fikret the smiling bodybuilder in Suada's journey - Hamer, Petra (Anthropological notebooks, 2025)
This article examines the agency of a deceased husband as it continues to affect his former wife’s life. Over thirty years have passed since he became one of the countless vic-tims of violence during the war in Bosnia-Herzegovina in the 1990s. Today, his wife keeps a memorial room in their hometown, preserving his memory as the first and most celebrated Bosnian bodybuilder, and ensuring that his legacy endures. These continuing bonds serve as both a mourning process and a celebration of his life. Two forms of agency of the dead are presented in the article: material and spiritual. The material agency is expressed through physical markers of remembrance such as the tombstone, the memorial room, and the commemorative plaque. The spiritual agency manifests in the dreams his wife experiences, which provide her with a sense of connection and guidance. This analysis examines the agency of the dead through the individual act of maintaining bonds with the deceased, while situating the narrative within the broader context of Verdery’s concept of the politicization of dead bodies. This approach high-lights how personal mourning intertwines with collective memory and cultural significance.
Keywords: agency of the dead; Bosna in Hercegovina; Bosnia and Herzegovina; continuing bonds; cultural anthropology; ethnology; etnologija; kulturna antropologija; memorialization; ohranjanje spomina; politicization; politizacija; Prijedor; trajne vezi; vloga mrtvih